SOCIAL CHANGES IN SUBURBAN COMMUNITY (Study In Saradan Vilage, Cibiru Subdistrict Of Bandung City) - Rica Arvenia; Muhammad Fadhil Nurdin; Muhammad Fedryansyah (Sosioglobal, 2020)
Traditional Sundanese suburban communitiesin protecting the territoryand the cultural preserver is not afraid of change. Because of, as a traditional society the community has the power to remain in their territory. This condition was found in the community of Saradan Village, Cibiru Sub-District of Bandung City. This study examines the social life of traditional Sundanese suburban communities, observes the changes in community life patterns that occur in the midst of rampant development. The purpose of this study is to determine the extent of the process of change in the life of the traditional Sundanese suburban of Saradan Village. This study uses a qualitative method with descriptive analysis which aims to describe the overall research problem. With a descriptive approach and in-depth interviews, showing that the existence of the community to maintain the heritage of the ancestors from time immemorial, the house and the land is one of the assets that must be maintained by the community. Changes in social and agriculture work in the community that are not always ongoing thinking is progressing, patterns of money in the cultural preservation aspects are still taking priority in the recognized communities as societies of the people who are polite and supportive. The dimensions of community life are difficult to penetrate by other communities, Sundanese people have a principle in themselves to not be easily influenced in action